Incidence of aortic stenosis in subjects with normal and slightly elevated aortic gradients and flow - Eveborn, Gry Wisthus; Schirmer, Henrik; Heggelund, Geir; Rasmussen, Knut (Heart (British Cardiac Society), 2015)
ObjectiveWe aimed to describe the progression rate into manifest aortic stenosis (AS) in subjects with normal aortic valves or in an early phase of calcific aortic valve disease.MethodsParticipants were recruited from the Tromsø Study, a population-based health survey. In our prospective cohort study, we performed two echocardiographical examinations (2001 and 2008) of a random sample of 1884 participants. AS was defined as a mean aortic valve gradient ≥15 mm Hg or a peak flow exceeding 2.6 m/s. Those with lesser values were stratified into three groups based on mean gradients (cut-off 5 and 10 mm Hg) and peak aortic flow (cut-off 1.5 and 2 m/s).ResultsAt baseline, 71 participants had gradients from 10 to 14.9 mm Hg, of whom 32.4% developed AS during follow-up. AS developed in only 3.6% of those with a baseline gradient of 5–9.9 mm Hg and in 0.3% of those with a gradient <5 mm Hg. Almost identical separations were obtained among the three flow velocity groups. Of the 45 subjects who developed incident AS, 56% acquired mild, 33% moderate and 11% severe AS. Their mean gradient progression rate was 2.7 mm Hg/year.ConclusionsThe results support that subjects with a mean aortic valve gradient of 10–15 mm Hg or aortic flow >2.0 m/s should be followed routinely. This group identifies about half of those who develop AS in the following 7 years.